1986
DOI: 10.1021/bi00372a047
|View full text |Cite
|
Sign up to set email alerts
|

Modified activity of Aeromonas aminopeptidase: metal ion substitutions and role of substrates

Abstract: Aeromonas aminopeptidase contains two nonidentical metal binding sites that have been shown by both spectroscopy and kinetics to be capable of interacting with one another [Prescott, J.M., Wagner, F.W., Holmquist, B., & Vallee, B.L. (1985) Biochemistry 24, 5350-5356]. The effects of metal ion substitutions on the susceptibility of the p-nitroanilides of L-alanine, L-valine, and L-leucine--substrates that are hydrolyzed at widely differing rates by native Aeromonas aminopeptidase--were studied by determining va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 17 publications
3
35
0
1
Order By: Relevance
“…A few Cu 2+ -substituted Zn hydrolases, including Aeromonas aminopeptidase (aAP) [48], astacin [53], and serralysin, also exhibit significant activities, which further corroborates the theory. Di-Cu-aAP exhibits only 5% and 9%, respectively, activities in terms of k cat and k cat /K m toward the hydrolysis of the specific substrate Leu-pNA [48], while Cu 2+ -astacin shows 37% activity in terms of k cat /K m toward succinyl-tri-Ala-pNA hydrolysis [53]. Despite the high Lewis acidity of Cu 2+ , almost all Cu 2+ -substituted derivatives of Zn hydrolytic enzymes are inactive or exhibit much lower activities than the native enzymes [32,44].…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…A few Cu 2+ -substituted Zn hydrolases, including Aeromonas aminopeptidase (aAP) [48], astacin [53], and serralysin, also exhibit significant activities, which further corroborates the theory. Di-Cu-aAP exhibits only 5% and 9%, respectively, activities in terms of k cat and k cat /K m toward the hydrolysis of the specific substrate Leu-pNA [48], while Cu 2+ -astacin shows 37% activity in terms of k cat /K m toward succinyl-tri-Ala-pNA hydrolysis [53]. Despite the high Lewis acidity of Cu 2+ , almost all Cu 2+ -substituted derivatives of Zn hydrolytic enzymes are inactive or exhibit much lower activities than the native enzymes [32,44].…”
Section: Resultssupporting
confidence: 55%
“…Consequently, several synthetic Cu 2+ complexes with high Lewis acidity have been demonstrated to catalyze hydrolytic reactions [45,46,47]. A few Cu 2+ -substituted Zn hydrolases, including Aeromonas aminopeptidase (aAP) [48], astacin [53], and serralysin, also exhibit significant activities, which further corroborates the theory. Di-Cu-aAP exhibits only 5% and 9%, respectively, activities in terms of k cat and k cat /K m toward the hydrolysis of the specific substrate Leu-pNA [48], while Cu 2+ -astacin shows 37% activity in terms of k cat /K m toward succinyl-tri-Ala-pNA hydrolysis [53].…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Mutations in Tyr 246 of S. griseus aminopeptidase and Tyr 552 of glutamate carboxypeptidase G II, which are located in the position of His 228Ј in CN2, resulted in about 100-and 10-fold reduction of activity, respectively (41,42), indicating that the residues are essential in the hydrolysis reaction in these peptidases. In the crystal structure of PepV in complex with a phosphinic inhibitor Asp⌿[PO 2 (7,44). A comparison of the active center of CN2 with those of M28 metallopeptidase family proteins revealed that the ligand residues and catalytic Glu are located in the same positions.…”
Section: Discussionmentioning
confidence: 99%